Rapid posterior capsular opacification in two patients treated for negative dysphotopsias - Juan Carlos Navia; Jordan J. Huang; Joaquin A. Reategui; Jaime D. Martinez (BMC Ophthalmology)
Abstract Background Negative dysphotopsias (ND) are visual aberrations associated with in-the-bag optic intraocular lens (IOL) placement, causing arc-shaped or linear shadows. Reverse optic capture (ROC) is employed to prevent ND, yet it poses the risk of posterior capsular opacification (PCO) which usually develops within 2–5 years post-surgery due to the lens epithelial cells (LECs) proliferation and migration onto the posterior capsule. This can lead to a cloudy or hazy appearance in the visual field. Early identification of posterior capsular opacities is crucial to ensure timely intervention and minimize visual impairment. Cases presentations We detail the management of two cases of acute and rapidly progressive PCO two weeks post-cataract extraction (CE) and IOL placement in patients with a prior history of ND at the Bascom Palmer Eye Institute. To prevent the development of ND in the subsequent eye, both patients underwent the ROC technique, in which a 3-piece intraocular lens with silicone aspheric neutral optics (SofPort LI61AOR2300 Bausch & Lomb Inc.) was inserted. At two-weeks post-operation, both patients reported a significant progressive decrease in vision in the treated eye, and severe posterior capsular opacities were observed. A diagnosis of PCO was confirmed, and successful visual rehabilitation was achieved through the performance of a neodymium-doped yttrium aluminum garnet (ND: YAG) laser capsulotomy without complications. This case series represents the first reported instances of patients developing PCO within two weeks of CE and IOL placement using the ROC technique. Conclusions This case series sheds light on the occurrence of posterior capsular opacities shortly after CE and IOL placement using the ROC technique. It highlights the importance of preoperative patient education, postoperative monitoring, and prompt management of potential complications in cataract surgery.